Students' interest in Arabic language learning: The roles of teacher - Juryatina Juryatina; Amrin Amrin (Journal of Educational Management and Instruction (JEMIN), 2021)
Arabic language education is a compulsory subject in Madrasah (Primary education level) under the auspices of the Ministry of Religious affairs. The students’ interest in Arabic language learning in Madrasah Aliyah Nurul Haq Rite Indonesia was very low. This is due to the students’ dislike of Arabic that demands the students to think, memorize, and be proficient in speaking as well as other skills. The current learning activities are non-varied and teacher-centered learning models. This study aims to determine the role of teachers in increasing students’ interest in Arabic learning. This study used a qualitative approach with field studies. Data collection techniques were interview, observation, and documentation. The data analysis techniques were in the form of data reduction, data display, and conclusion drawing. The results of this study on the roles of teachers indicate that; (1) the teacher provides motivation and guidance for every Monday ceremony and Imtaq activities on Friday, (2) the teacher only uses textbooks without semester learning plans and other learning tools, (3) the teacher uses non-varied methods ( such as the lecture and discussion method), (4) the teacher provides an assessment of learning outcomes, (5) the teacher provides evaluation or tests, (6) the teacher gives praise to students, and (7) the teacher punishes students who do not do assignments. The results of this study contribute as practical insights for teachers, especially Arabic teachers in maximizing their roles to increase interest in learning Arabic in schools.